2010
DOI: 10.1074/jbc.c110.147470
|View full text |Cite
|
Sign up to set email alerts
|

The Peptidomimetic CXCR4 Antagonist TC14012 Recruits β-Arrestin to CXCR7

Abstract: CXCR7 is an atypical chemokine receptor that signals through ␤-arrestin in response to agonists without detectable activation of heterotrimeric G-proteins. Its cognate chemokine ligand CXCL12 also binds CXCR4, a chemokine receptor of considerable clinical interest. Here we report that TC14012, a peptidomimetic inverse agonist of CXCR4, is an agonist on CXCR7. The potency of ␤-arrestin recruitment to CXCR7 by TC14012 is much higher than that of the previously reported CXCR4 antagonist AMD3100 and differs only b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 29 publications
4
88
0
Order By: Relevance
“…Little is known about structural elements underlying the different receptor functions (16,22,40). By generating tailswap mutant CXCR4 and CXCR7 receptors, we provide evidence that replacement of the CXCR7 C terminus with the CXCR4 C terminus generates a CXCR7 chimera, which shows CXCL12-dependent internalization and CXCL12-dependent phosphorylation but lacks ligand-independent internalization.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Little is known about structural elements underlying the different receptor functions (16,22,40). By generating tailswap mutant CXCR4 and CXCR7 receptors, we provide evidence that replacement of the CXCR7 C terminus with the CXCR4 C terminus generates a CXCR7 chimera, which shows CXCL12-dependent internalization and CXCL12-dependent phosphorylation but lacks ligand-independent internalization.…”
Section: Discussionmentioning
confidence: 92%
“…In the case of the atypical chemokine receptor D6, constitutive phosphorylation of a cluster of serine residues in the C terminus has been shown to be involved in ␤-arrestin recruitment, receptor trafficking, and receptor stability (24). Thus, the presence of potential phosphorylation sites in the C-terminal domain of CXCR7 suggests that a similar mechanism may be involved in trafficking and MAP kinase sig-naling of CXCR7 (11,22,40). Our finding that the CXCR4 C terminus shows strong constitutive phosphorylation when fused to CXCR7 points to the possibility that the CXCR7 protein prefers a conformation that attracts G protein-coupled receptor kinases.…”
Section: Discussionmentioning
confidence: 99%
“…However, CXCR7 is an atypical chemokine receptor that apparently does not signal through canonical G protein-linked signaling pathways even in the presence of saturating SDF-1 concentrations (11,12,14,15). Even though the signaling pathways activated by CXCR7 are still under investigation, there is increasing evidence that CXCR7 may function as a biased receptor for selective recruitment and activation of ␤-arrestin-mediated signaling (23)(24)(25)32). In this study, we show that CXCR7 modulates CXCR4 function by self-assembling in cell membranes to form heterodimers or possibly higher order hetero-oligomers with CXCR4.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study conducted by Gravel et al (32) demonstrated that a chimeric CXCR7 bearing the C-terminal tail of CXCR4 resulted in constitutive recruitment of ␤-arrestin. Such recent studies have demonstrated the usefulness of bioluminescence resonance energy transfer, luciferase complementation, and imaging techniques to investigate the ␤-arrestin-CXCR7 interaction (20,21,23,24,32). Although analogous bioluminescence resonance energy transfer/FRET techniques can be implemented to identify the specific partner of the CXCR4⅐CXCR7 dimer pair that plays a key role in ␤-arrestin recruitment, the localization and identification of amino acids involved in contacting ␤-arrestin may require more focused techniques such as unnatural amino acid mutagenesis, bio-orthogonal labeling, photochemical cross-linking, and reconstitution in membrane nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…β-arrestin-2 recruitment to CXCR4 was measured by an intermolecular BRET assay performed as described previously (27,38). The values were corrected to net BRET by subtracting the background BRET signal obtained in cells transfected with the Rluc construct alone.…”
Section: Methodsmentioning
confidence: 99%